Synthesis, structural characterization and mesomorphic properties of Schiff Base Copper (II) complex / Nur Syaza Sahira Ahmad Zaidi - Ahmad Zaidi, Nur Syaza Sahira (2023)
Metallomesogens are metal-containing liquid crystals. There is little known about metallomesogens derived from short-chain Schiff base ligands and long alkoxy groups. This research aims to learn more by developing a new metallomesogen with a short chain spacer and a substituent with a long alkoxy group that can be used to make low-cost electronic devices.The main objective of this research project was to synthesis and characterized the structure of Schiff base ligand and its Cu(II) complexes (CuL and CuLC10), and study the thermal stability and mesomorphic behaviour for the Cu(II) complex. In this study, Cu(II) complex (CuL) and its Schiff base ligand (H2L) were successfully synthesized by using ethanol as a solvent. Besides, a new metallomesogen derived from salen Schiff base ligand with two carbon chain substituent with the long terminal end alkoxy group (decane) coordinated with Cu(II) metal (CuLC10) was also synthesized by reacting Cu(II) complex (CuL) with 1-bromodecane in ethanol as solvent by refluxing for 4 hours. The structure of Schiff base ligand (H2L) was characterized by using FTIR and 1HNMR spectroscopy while its complexes (CuL and CuLC10) was characterized by using FTIR spectroscopy and the geometry of the metal centre was determined by using UV-Vis spectroscopy. As for the thermal properties, magnetic properties, and mesomorphic properties studies of the Cu(II) complex, CuLC10 were conducted using TGA, magnetic susceptibility and DSC as well as OPM instrumental analysis respectively. Based on the FTIR spectroscopy, both Cu(II) complexes (CuL and CuLC10) shows the existence of acetate ion (CH3COO-) in chelating binding mode. The UV-Vis for both complexes indicate the geometry of the metal centre of square planar. As for the Cu(II) complex of CuLC10 was expected to have mesomorphic properties and perhaps with high thermal stability. However, the synthesized Cu(II) complex (CuLC10) in this research project does not shows any mesomorphism properties and have thermal stability only up to 64 ̊C based on the TGA, DSC and OPM analysis studies. This is because the CuLC10 complex shows no coordination of the CuL with long alkyloxy chain based on the analysis of FTIR and TGA data. Furthermore, the study using magnetic susceptibility instrumental analysis shows that the CuLC10 complex is paramagnetic and a dinuclear complex which contain two Cu(II) metal centres. Thus, the Cu(II) complex, CuLC10 contain two Cu(II) metals as metal centres that bind with two acetate ion in chelating binding mode but the complex does not exhibit mesomorphism behaviour and have low thermal stability may be due to no coordination of the complex with long alkyloxy chain tail as its substitute which causing the structure of the complex to be rigid but not elongated.